Facial memory ability and self-awareness in patients with temporal lobe epilepsy after anterior temporal lobectomy - Hosokawa, Hiroaki (PLoS One, 2021)
Anterior temporal lobectomy (ATL) is the most common surgical treatment for drug-resistant temporal lobe epilepsy (TLE). Right ATL has been reported to reduce facial memory ability in patients with TLE, as indicated by poor performance on the Warrington Recognition Memory Test for Faces (RMF), which is commonly used to evaluate visual memory in these patients. However, little is known about whether patients with TLE exhibit difficulties in identifying faces in daily life after ATL. The aim of this study was to investigate facial memory ability and self-awareness of face identification difficulties in patients with TLE after ATL. Sixteen patients with TLE after right ATL, 14 patients with TLE after left ATL, and 29 healthy controls were enrolled in this study. We developed the multiview face recognition test (MFRT), which comprises a learning phase (one or three frontal face images without external facial feature information) and a recognition phase (frontal, oblique, or noise-masked face images). Facial memory abilities were examined in all participants using the MFRT and RMF, and self-awareness of difficulties in face identification was evaluated using the 20-item prosopagnosia index (PI20), which has been widely used to assess developmental prosopagnosia. The MFRT performance in patients with TLE after ATL was significantly worse than that in healthy controls regardless of the resected side, whereas the RMF scores in patients with TLE were significantly worse than those in healthy controls only after right ATL. The MFRT performance in patients with TLE after both left and right ATL was more influenced by working memory load than that in healthy controls. The PI20 scores revealed that patients with TLE after left ATL were aware of their difficulties in identifying faces. These findings suggest that patients with TLE not only after right ATL but also after left ATL might have difficulties in face identification.